Proceedings of the 28th ACM SIGPLAN Conference on Programming Language Design and Implementation 2007
DOI: 10.1145/1250734.1250738
|View full text |Cite
|
Sign up to set email alerts
|

Automatically classifying benign and harmful data races using replay analysis

Abstract: Many concurrency bugs in multi-threaded programs are due to data races. There have been many efforts to develop static and dynamic mechanisms to automatically find the data races. Most of the prior work has focused on finding the data races and eliminating the false positives.In this paper, we instead focus on a dynamic analysis technique to automatically classify the data races into two categories -the data races that are potentially benign and the data races that are potentially harmful. A harmful data race … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(101 citation statements)
references
References 42 publications
3
97
0
Order By: Relevance
“…Furthermore, even true data races can be benign and would not do any harm to the system operation. It has been reported that the amount of such harmless data races can be so big as 76%-90% of the true data races reported by the modern detectors [25], which calls for a sophisticated detection mechanism for distinguishing harmful races over harmless ones [26].…”
Section: Accuracymentioning
confidence: 99%
“…Furthermore, even true data races can be benign and would not do any harm to the system operation. It has been reported that the amount of such harmless data races can be so big as 76%-90% of the true data races reported by the modern detectors [25], which calls for a sophisticated detection mechanism for distinguishing harmful races over harmless ones [26].…”
Section: Accuracymentioning
confidence: 99%
“…This simple idea for classifying the characteristic of data races is used in Ref. [4]. We extend it for the distinction of benign and conflicting synchronization pair.…”
Section: Finding (4)mentioning
confidence: 99%
“…A data race often occurs in the scenario where more than two different threads, at least one of which is writing the value, access the same shared memory location without appropriate synchronization [1]. Despite the destructiveness of data races (e.g., Northeast blackout 1) and Therac-25 accidents 2) ), current thread specifications of C 3) and C++ 4) still permit the existence of data races intentionally for the sake of better program performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this situation, even though a race occurs by definition (the shared variable flag is written and read without explicit synchronization), it does not harm the program. Narayanasamy et al [40] show other types of benign symmetric races, e.g., redundant writes and disjoint bit manipulation.…”
Section: Symmetric Races Are Usually Benignmentioning
confidence: 99%